Distributed and Adaptive Efficient Energy Aware Routing Procedure for MANETs - Santhi Sri, T; Rajendra Prasad, J; Kiran Kumar, R (International Journal of Engineering and Technology, 2018)
In mobile ad hoc networks MANET, power or energy consumption is a complex representation to define extensive communication between different nodes. To define energy routing scenario with respect to efficient energy maintenance to decrease the over burden of the protocol hierarchy wireless communication. To achieve these goals, a Synchronization-based Efficient Energy (SEE) calculation is supported along with the position opportunistic routing protocol previously to reduce overhead burden of server to maintain efficient energy. It consists distributed and random nature in which node consists local communication by facilitate packet transmitting in between different intermediate nodes based on backward communication. Because of random routing scenario of ad hoc networks, maintenance of capacity of each node for relay configuration at each node is a complex task. Due to that further extension of SEE, we introduce Collaborative & Efficient Energy Aware Distributed (CEEAD) approach, which consists routing representation in energy awareness scenario for wireless networks and it also supports cluster head representation of each node based on its random changes of power consumption in network communication. Our proposed approach consists cluster connectivity at each node because random routing process for wireless ad hoc networks. Our experimental results show effective increasing of network life time with scalable data communication in wireless networks.Â Â Â